An efficient strategy for generation of transgenic mice by lentiviral transduction of male germline stem cells in vivo. Issue 1 (December 2015) - Qin, Jinzhou; Xu, Haixia; Zhang, Pengfei; Zhang, Conghui; Zhu, Zhendong; Qu, Rongfeng; Qin, Yuwei; Zeng, Wenxian
Abstract Background Male germline stem cells (MGSCs) are a subpopulation of germ cells in the testis tissue. MGSCs are capable of differentiation into spermatozoa and thus are perfect targets for genomic manipulation to generate transgenic animals. Method The present study was to optimize a protocol of production of transgenic mice through transduction of MGSCsin vivo using lentiviral-based vectors. The recombinant lentiviral vectors with either EF-1 or CMV promoter to drive the expression of enhanced green fluorescent protein (eGFP) transgene were injected into seminiferous tubules or inter-tubular space of 7-day-old and 28-day-old mouse testes. At 5 or 6 wk post-surgery, these pre-founders were mated with wild-type C57BL/6J female mice (1.5 to 2.0-month-old). Results Sixty-seven percent of F1 generation and 55.56 % of F2 offspring were positive for eGFP transgene under the control of EF-1 promoter via PCR analysis. The transgenic pups were generated in an injection site-and age-independent manner. The expression of transgene was displayed in the progeny derived from lentiviral vector containing CMV promoter to drive transgene, but it was silenced or undetectable in the offspring derived from lentiviral vector with transgene under EF-1 promoter. The methylation level of gDNA in the promoter region of transgene was much higher in the samples derived lentiviral vectors with EF-1 promoter than that with CMV promoter, suggesting eGFP transgene was suppressed by DNA methylationin vivo . Conclusion This research reported here an effective strategy for generation of transgenic mice through transduction of MGSCsin vivo using lentivirus vectors with specific promoters, and the transgenic offspring were obtained in an injection site-and age-independent manner. This protocol could be applied to other animal species, leading to advancement of animal transgenesis in agricultural and biomedical fields.